Expression of human beta-defensins-1–4 in thyroid cancer cells and new insight on biologic activity of hBD-2 in vitro - Zhuravel, O.V.; Gerashchenko, O.L.; Khetsuriani, M.R.; Soldatkina, M.A.; Pogrebnoy, P.V. (Experimental Oncology, 2014)
The study was aimed on analysis of human beta-defensin-1–4 (hBDs) mRNA expression in cultured thyroid cancer cells and evaluation of effects of recombinant hBD-2 (rec-hBD-2) on growth patterns, migration properties and expression of E-cadherin and vimentin in these cells. Methods: The study was performed on cultured follicular thyroid cancer WRO cells, papillary thyroid cancer TPC1 cells, and anaplastic thyroid cancer KTC-2 cells. For analysis of hBD-1–4 mRNA expression in thyroid cancer cells, semiquantitative RT-PCR was used. Effects of rec-hBD-2 on cell proliferation, viability, and migration were analyzed using direct cell counting, MTT test, and scratch assay respectively. Expression of vimentin and E-cadherin was evaluated by quantitative PCR (qPCR). Results: By the data of RT-PCR, all three studied thyroid cancer cell lines express hBD-1 and -4 mRNA, but not hBD-2 mRNA, while hBD-3 expression was detected in WRO and KTC-2 cells. The treatment of TPC-1, WRO, and KTC-2 cells with 100–1000 nM rec-hBD-2 resulted in significant concentration-dependent suppression of cell proliferation, viability, and migratory property. By the data of qPCR, significant up-regulation of vimentin expression was registered in KTC-2 and WRO cells treated with 500 nM rec-hBD-2. Significant down-regulation of E-cadherin expression (p < 0.05) was detected only in KTC-2 cells treated with the defensin. Also, it has been shown that TPC-1 cells treated with 500 nM rec-hBD-2 acquired more elongated morphology. Conclusion: The data demonstrate that hBD-2 in concentrations higher than 100 nM exerts significant concentration-dependent suppression of thyroid cancer cell growth and migration, and affects vimentin and E-cadherin expression dependent on histologic type of thyroid cancer cells. Key Words: thyroid cancer, human beta-defensin-2, E-cadherin, vimentin, proliferation, viability.